Global-scale analysis of socioeconomic impacts of coastal flooding over the 21st century - Kirezci, Ebru; Young, Ian R.; Ranasinghe, Roshanka; Lincke, Daniel; Hinkel, Jochen (Frontiers in Marine Science, 2023)
Building on a global database of projected extreme coastal flooding over the coming century, an extensive analysis that accounts for both existing levels of coastal defences (structural measures) and two scenarios for future changes in defence levels is undertaken to determine future expected annual people affected (EAPA) and expected annual damage (EAD). A range of plausible future climate change scenarios is considered along with narratives for socioeconomic change. We find that with no further adaptation, global EAPA could increase from 34M people/year in 2015 to 246M people/year by 2100. Global EAD could increase from 0.3% of global GDP today to 2.9% by 2100. If, however, coastal defences are increased at a rate which matches the projected increase in extreme sea level, by 2100, the total EAPA is reduced to 119M people/year and the EAD will be reduced by a factor of almost three to 1.1% of GDP. The impacts of such flooding will disproportionately affect the developing world. By 2100, Asia, West Africa and Egypt will be the regions most impacted. If no adaptation actions are taken, many developing nations will experience EAD greater than 5% of GDP, whilst almost all developed nations will experience EAD less than 3% of GDP.